Students' Critical Thinking Skills in Islamic Schools: The Effect of Problem-Based Learning (PBL) Model - Kamil, Badrul; Velina, Yessy; Kamelia, Marlina (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2019)
Industrial Revolution 4.0 requires schools to produce graduates who are not only good in memorizing various materials, but also must have the skills to think critically. Problem-Based Learning (PBL) is one of the learning models that is deemed good in training students' critical thinking skills, including students in Islamic schools. The purpose of this research is to determine the effect of problem-based learning on students' critical thinking skills in Islamic schools. This type of research is a quasi-experimental with random sampling as the sampling technique. The research sample was 66 students. Data collection uses instruments in the form of description tests that are adjusted to the indicators of critical thinking skills. The research analysis technique used was the t-test to determine the effect of the problem-based learning model on students' critical thinking skills. The result of the research shows that the average score of the class where the critical thinking skills through PBL are applied is higher than the class that does not apply PBL. The result of the data analysis using the t-test obtained that the value of tcount bigger ttable is 4.119 > 1.997 with a significance level of 5 %, so it is said that the PBL model influences students' critical thinking skills. It is suggested to make PBL learning becomes a mandatory choice to be applied in the learning process with the learning steps that have an impact on the students' thinking process.